Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/10711007211034849
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Distal Metatarsal Metaphyseal Osteotomy of the Lesser Toes: Clinical, Radiologic, and Pedobarographic Outcomes

Abstract: Background: The minimally invasive distal metatarsal metaphyseal osteotomy (DMMO) is a percutaneous operative technique with the aim to relieve the symptoms of metatarsalgia. To our knowledge, no previous research has analyzed both pre- and postoperative pedobarographic data including the changes in plantar pressure. Methods: Thirty patients (31 feet) were operated on with a DMMO and included in a prospective study. Clinical, radiologic, and pedobarographic outcomes were evaluated in comparison with the preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Minimally invasive techniques involving the lesser metatarsals continue to grow in popularity. Neunteufel et al 1 reported a case series of 30 patients (31 feet) who underwent minimally invasive distal metatarsal metaphyseal osteotomy for metatarsalgia of ≥1 lesser metarsals 2-5 . All clinical scores (American Orthopaedic Foot & Ankle Society [AOFAS] Forefoot Score, Foot Function Index, Foot and Ankle Outcome Score [FAOS], and visual analog scale [VAS] pain score) improved significantly at a mean follow-up of 15.5 months.…”
Section: Forefootmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimally invasive techniques involving the lesser metatarsals continue to grow in popularity. Neunteufel et al 1 reported a case series of 30 patients (31 feet) who underwent minimally invasive distal metatarsal metaphyseal osteotomy for metatarsalgia of ≥1 lesser metarsals 2-5 . All clinical scores (American Orthopaedic Foot & Ankle Society [AOFAS] Forefoot Score, Foot Function Index, Foot and Ankle Outcome Score [FAOS], and visual analog scale [VAS] pain score) improved significantly at a mean follow-up of 15.5 months.…”
Section: Forefootmentioning
confidence: 99%
“…Walter C. Hembree, MD1 Mitchell C. Tarka, MD1 Jordan B. Pasternack, MD 1 Smitha E. Mathew, MBBS1 Gregory P. Guyton, MD1 1 Department of Orthopaedic Surgery, MedStar Union Memorial Hospital, Baltimore, Maryland Email for corresponding author: gpguyton@gmail.com…”
mentioning
confidence: 99%
“…We were delighted to see this paper from Vienna (Austria) , where the team objectively reviewed and reported the results of their prospective series to enrich us with a suitable piece of objective evidence. 1 Patients with metatarsalgia of the lesser rays who failed conservative therapy for over a year were offered DMMO. Those with subluxation of one of the lesser metatarsophalangeal (MTP) joints, peripheral vascular disease, inflammatory arthropathy, and peripheral neuropathy (including metatarsalgia associated with Charcot arthropathy) were excluded from the report.…”
Section: Minimally Invasive Distal Metatarsal Metaphyseal Osteotomy: ...mentioning
confidence: 99%